Structure and organizational design of the school of automobile education Conduser, in Dosquebradas (2020)
The present paper work intends to know the structure and organizational design of the Conduser School of Automotive Education, from the description of concepts that are considered fundamental to make possible the investigation. Those concepts correspond to: organization, strategy, organizational design, organizational structure and direction. In the first instant, there will be made a count of the concepts already mentioned to get in context. Next, there will be some theories used that contribute to the understanding of the administrative perspective of work, in which is describe how a company makes its process to accomplish its targets from the organizational design and structure and how the purposes of the organization are stablished by the high direction. From accounting part, it will tell what the process is and rules stablished and required internationally to carry the accounting of all the companies. On the other hand, the next part will be to describe the company in which the investigation was made and what is the process that follows for decision making, its objectives and the activities that it makes as a strategy for the accomplish of those and stand out from the competence. To finish, the findings are described from a non-structured interview that was made to the administrator of Conduser, this way was able to get the identification of the elements that sum up to the maintenance inside of the market and the sources used for decision making, as well as accentuation of goals and strategies, it means, how is build the structure and design of Conduser